2020
DOI: 10.1038/s41598-020-72272-4
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopic lobectomy is feasible for selected patients with clinical N2 non-small cell lung cancer

Abstract: Few studies have evaluated the usefulness of video-assisted thoracoscopic surgery (VATS) for advanced-stage lung cancer. We aimed to evaluate the feasibility of VATS for treating clinical N2 (cN2) lung cancer. A retrospective cohort analysis was performed with data from 268 patients who underwent lobectomy for cN2 disease from 2007 to 2016. Using propensity score-based inverse probability of treatment weighting (IPTW), perioperative and long-term survival outcomes were compared. We performed VATS and open thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…17 Our meta-analysis also showed that VATS approach could achieve comparable short-term and long-term clinical outcomes to thoracotomy for cN0-pN2 NSCLC. For NSCLC patients with mediastinal lymph node metastasis, several factors including inadequate experience during training, 35 narrow visual field with limited range of instrumental movement, 36 and inferior oncological effectiveness (e.g., lymph node assessment) may contribute to the major concerns of VATS for pN2 NSCLC. 21,37 However, Li et al 26 performed a retrospective analysis of 76 patients comparing clinical outcomes for patients with clinical N0, but pathologic N2 NSCLC patients after VATS lobectomy and thoracotomy lobectomy, they F I G U R E 4 Forest plot of (a) 1-year OS, and (b) 3-year OS; PSM, propensity score matched; VATS, video-assisted thoracoscopic surgery; OS, overall survival; CI, confidence interval found that VATS approach could yield similar total number of dissected mediastinal lymph node and the total number of dissected lymph node stations.…”
Section: Discussionmentioning
confidence: 99%
“…17 Our meta-analysis also showed that VATS approach could achieve comparable short-term and long-term clinical outcomes to thoracotomy for cN0-pN2 NSCLC. For NSCLC patients with mediastinal lymph node metastasis, several factors including inadequate experience during training, 35 narrow visual field with limited range of instrumental movement, 36 and inferior oncological effectiveness (e.g., lymph node assessment) may contribute to the major concerns of VATS for pN2 NSCLC. 21,37 However, Li et al 26 performed a retrospective analysis of 76 patients comparing clinical outcomes for patients with clinical N0, but pathologic N2 NSCLC patients after VATS lobectomy and thoracotomy lobectomy, they F I G U R E 4 Forest plot of (a) 1-year OS, and (b) 3-year OS; PSM, propensity score matched; VATS, video-assisted thoracoscopic surgery; OS, overall survival; CI, confidence interval found that VATS approach could yield similar total number of dissected mediastinal lymph node and the total number of dissected lymph node stations.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing enhancement of equipment and technology, VATL could greatly lower the incidence of mortality and complications. [ 7 , 17 , 18 ] However, patients may still suffer from CPSP. CPSP refers to the continuous or intermittent pain, mainly caused by surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Lobectomy is an important treatment for patients with NSCLC lung cancer. With the increasing enhancement of equipment and technology, VATL could greatly lower the incidence of mortality and complications [7,17,18] . However, patients may still suffer from CPSP.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of stage IA NSCLC patients who underwent lobectomy demonstrated that VATS was associated with increased 5-year OS compared to open thoracotomy (100% vs. 87%, p = 0.01) and DFS (100% vs. 86%, p = 0.03) ( 63 ). In tumors greater than 5 cm, VATS was associated with greater OS and DFS ( p = 0.056 and 0.031, respectively) compared to open thoracotomy ( 64 ), and in clinical N2 lung cancer, VATS showed similar 5-year OS (50.5% vs. 48.4%, p = 0.127) and DFS (60.5% vs. 44.6%, p = 0.069) ( 65 ). A study of oncological outcomes in patients who underwent surgical resection for early-stage lung cancer found no differences in 5-year OS (71.6% vs. 65.9%, p = 0.36) and DFS (75.2% vs. 69.2%, p = 0.55) between VATS and open lobectomy ( 66 ).…”
Section: Perioperative Modulation Of Inflammatory Response and Oncolo...mentioning
confidence: 99%